The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1039/c7fo00452d
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of curcumin microcrystals and evaluation of the antimicrobial and sensory aspects in minimally processed carrots

Abstract: Nontoxic conserving agents are in demand by the food industry due to consumers concern about synthetic conservatives, especially in minimally processed food. The antimicrobial activity of curcumin, a natural phenolic compound, has been extensively investigated but hydrophobicity is an issue when applying curcumin to foodstuff. The objective of this work was to evaluate curcumin microcrystals as an antimicrobial agent in minimally processed carrots. The antimicrobial activity of curcumin microcrystals was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Other authors have also reported a high sensitivity of these pathogens to curcumin, although the above-mentioned species have been examined to varying degrees. A lot of data exists for S. aureus (e.g., [ 20 , 32 , 34 , 35 , 37 , 54 ]), while in the case of S. pyogenes [ 20 , 31 , 33 , 55 ], and A. lwoffii [ 20 ], they are few. The very strong antimicrobial activity of curcumin, probably due to the use of acetone as a solvent, was shown in the studies of Lutomski et al [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have also reported a high sensitivity of these pathogens to curcumin, although the above-mentioned species have been examined to varying degrees. A lot of data exists for S. aureus (e.g., [ 20 , 32 , 34 , 35 , 37 , 54 ]), while in the case of S. pyogenes [ 20 , 31 , 33 , 55 ], and A. lwoffii [ 20 ], they are few. The very strong antimicrobial activity of curcumin, probably due to the use of acetone as a solvent, was shown in the studies of Lutomski et al [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In turn, this activity of curcumin against such bacteria as A. lwoffii [ 20 ], Proteus mirabilis [ 24 , 30 ], Serratia marcescens [ 20 , 24 ], Stenotrophomonas maltophilia [ 31 ], and Streptococcus agalactiae [ 30 ] has been examined sporadically. In the contemporary research, the in vitro ability of curcumin to inhibit microbial growth has frequently been tested against a small (4–6) number of species representing a small group of taxa, mostly E. coli , P. aeruginosa , and S. aureus , and less often Bacillus subtilis and Enterococcus faecalis (e.g., [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ]). Some works have reported the minimum inhibitory concentration (MIC) value for only one species and a single, usually reference, strain (e.g., [ 39 , 40 , 41 , 42 ]).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with the literature, our results showed that curcumin wine solution should be an alternative to prolong the shelf life of oysters. Da Silva et al () evaluated the antimicrobial activity of curcumin microcrystals in minimally processed carrots, with a concentration of 1.3 ± 0.6 mg curcumin/g carrot. Curcumin microcrystals significantly reduced the count of total psychrophilic and mesophilic microorganisms during 15 days of storage.…”
Section: Resultsmentioning
confidence: 99%
“…Bellary, Indiramma, Prakash, Sowbhagya, and Rastogi (2017) used curcumin as a natural dye on coconut slices and banana slices; Kaba, Özer, and Çorapcı (2017) used curcumin on smoked fish as a natural colorant. Da Silva et al (2017) used curcumin as a natural antimicrobial agent on freshly cut carrots.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin is a polyphenol with remarkable properties like endogenous antioxidant (Jaiswal et al, 2016), anti-inflammatory (Aggarwal and Harikumar, 2009), and antimicrobial activities (Bajpai et al, 2015;da Silva et al, 2017), together with the ability to modulate the action of important enzymes like the ones involved in the cholinergic equilibrium (Ahmed and Gilani, 2009). Curcumin bioactivity has been subjected to extensive studies and reviewed in detail (Prasad et al, 2014), but only recently its colorant ability caught the attention of the industrial sector, particularly the food industry, which urges for alternatives to synthetic colorants.…”
Section: Introductionmentioning
confidence: 99%